Stimulatory effect of the ethanol extract of Melastoma malabathricum L. (Melastomataceae) leaf on the reproductive system of male albino rats - K. Balamurugan, G. Sakthidevi and V. R. Mohan (Journal of Applied Pharmaceutical Science, 2013)
Fertility enhancement effect of ethanol extract of leaf of Melastoma malabathricum was observed in male albino rats. The relative weight of the testis and epididymis were increased. The epididymal sperm count, motility and sperm abnormality were increased significantly in treated rats. There was an increase in serum protein, albumin, globulin, urea, creatinine and the activity of liver marker enzymes (SGOT, SGPT and ALP) levels of treated rats. The activities of serum antioxidants (CAT, SOD. GPX, GST and GRD) in leaf extract treated rats were increased. The results of the hormonal assay showed that increased serum levels of LH and testosterone but decreased in the serum levels of FSH and estrogen compared to control. The results of fertility test indicated that the treated adult male rats increased the number of female’s impregnation. In addition, the number of implantations and the number of viable fetuses were also increased. The results of the present study concluded that, ethanol extract of leaf of Melastoma malabathricum enhanced sperm concentration, motility and testosterone which might produce positive result in the male fertility.
Keywords: Melastoma malabathricum, Fertilit